A Detailed Review on the Properties and Applications of WO3 Nanostructure-Based Optical and Electronic Devices - Yu Yao; Dandan Sang; Liangrui Zou; Qinglin Wang; Cailong Liu (Recent Trends in Chemical and Material Sciences Vol. 5, 2022)
Tungsten oxide (WO3) is a wide bandgap semiconductor exhibiting unintentionally doped n-type, excellent electrical conductivity and high electron Hall mobility, and is therefore considered as a candidate material for application in optoelectronics. Reviews on the applications of WO3 and its derivatives in electrochemistry, photochemistry, hybrid photocatalysts, electrochemical energy storage, and gas sensors have also been appearing recently. In addition, nanostructured transition metal oxides have attracted a lot of attention in the past decade due to their unique chemical, photochromic, and physical properties. And among these transition metal oxides, the applications of WO3 nanostructure-based optical and electronic devices have gradually attracted extensive research interest due to their unique photoluminescence (PL), electrochromic, and electrical properties. This review focuses on recent advances related to WO3, starting from fundamental analysis to improve the optoelectronic, electrochromic, and photochromic properties of WO3 and to develop advanced devices based on tungsten oxide for optical and electronic applications, including photodetectors, light-emitting diodes (LEDs), PL properties, electrical properties, and optical information storage. This review on the prior findings of WO3-related optical and electrical devices, as well as concluding remarks and forecasts will help researchers to advance the field of optoelectric applications of nanostructured transition metal oxides.